2023
DOI: 10.1021/jacs.2c12008
|View full text |Cite
|
Sign up to set email alerts
|

Generating Long-Lived Triplet Excited States in Narrow Bandgap Conjugated Polymers

Abstract: Narrow bandgap conjugated polymers are a heavily studied class of organic semiconductors, but their excited states usually have a very short lifetime, limiting their scope for applications. One approach to overcome the short lifetime is to populate long-lived triplet states for which relaxation to the ground state is forbidden. However, the triplet lifetime of narrow bandgap polymer films is typically limited to a few microseconds. Here, we investigated the effect of film morphology on triplet dynamics in rede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Due to the deshielding effect of the An approximately arranged by the π-stacking in PS-An , the chemical shift of protons in the pyran nitrile part of PS-An has significantly shifted toward the low field compared with that of PS-Be and p-PS-An . The π-stacked conformation could largely inhibit the molecular rotation and vibration and reduce the nonradiative inactivation of the excited states. ,,, Indeed, ascribed to the rigid plane of the unit Be , PS-Be behaved enhanced fluorescence quantum yield compared with PS (Table S1). Intuitively, PS-An with a bigger π-stacked rigid plane of An should have exhibited a higher fluorescence quantum yield than that of PS-Be .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the deshielding effect of the An approximately arranged by the π-stacking in PS-An , the chemical shift of protons in the pyran nitrile part of PS-An has significantly shifted toward the low field compared with that of PS-Be and p-PS-An . The π-stacked conformation could largely inhibit the molecular rotation and vibration and reduce the nonradiative inactivation of the excited states. ,,, Indeed, ascribed to the rigid plane of the unit Be , PS-Be behaved enhanced fluorescence quantum yield compared with PS (Table S1). Intuitively, PS-An with a bigger π-stacked rigid plane of An should have exhibited a higher fluorescence quantum yield than that of PS-Be .…”
Section: Resultsmentioning
confidence: 99%
“…The π-stacked conformation could largely inhibit the molecular rotation and vibration and reduce the nonradiative inactivation of the excited states. 36,37,35,38 Indeed, ascribed to the rigid plane of the unit Be, PS-Be behaved enhanced fluorescence quantum yield compared with PS 38 (Table S1).…”
mentioning
confidence: 99%
“…The small band gap value indicated that 2TP-BBT had a relatively broad solar absorption range. Generally, the molecules are in the ground state S 0 , and when 2TP-BBT absorbs the energy of excitation light, the electrons transition from the ground state to the lowest excited state (S 1 ) or the triple excitation state (T 1 ) 56,57 (Fig. S7 and S8, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the low‐energy triplets generated through SF are challenging to harness effectively [7] . An alternative and more commonly employed method for generating triplet excitons involves ISC, wherein the triplet state is directly produced from the singlet state [8,9] . However, ISC is generally slow, occurring on ns to microsecond (μs) timescales.…”
Section: Introductionmentioning
confidence: 99%
“…[7] An alternative and more commonly employed method for generating triplet excitons involves ISC, wherein the triplet state is directly produced from the singlet state. [8,9] However, ISC is generally slow, occurring on ns to microsecond (μs) timescales. As a result, ISC-based triplet materials often resort to incorporation of heavy atoms into conjugated compounds.…”
Section: Introductionmentioning
confidence: 99%